The Relationship Between Statin Action On Thyroid Autoimmunity And Vitamin D Status: A Pilot Study - Krysiak, Robert; Szkróbka, Witold; Okopień, Bogusław (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Both vitamin D preparations and high-dose statin therapy were found to reduce thyroid antibody titers.Objective The purpose of this study was to assess whether vitamin D status determines the effect of statin therapy on thyroid autoimmunity.Methods The study population consisted of 39 euthyroid women with Hashimoto's thyroiditis and moderate or moderately high cardiovascular risk divided into two groups: women with vitamin D deficiency or insufficiency (group A; n=19) and women with normal vitamin D status (group B, n=20). All patients received atorvastatin therapy (20–40 mg daily) for the following 6 months. Plasma lipids, circulating levels of thyrotropin, free thyroid hormones, prolactin and 25-hydroxyvitamin D, titers of thyroid peroxidase and thyroglobulin antibodies, as well as Jostel’s, the SPINA-GT and the SPINA-GD indices were assessed at the beginning and at the end of the study.Results The study completed all women. At baseline, with the exception of 25-hydroxyvitamin D, there were no significant differences between both study groups in plasma lipids, circulating hormone levels and titers of thyroid peroxidase and thyroglobulin antibodies. Despite improving plasma lipids in both study groups, atorvastatin reduced thyroid antibody titers only in women with normal vitamin D status. Moreover, in this group of patients, atorvastatin increased the SPINA-GT index. Circulating levels of the measured hormones, Jostel’s thyrotropin index and the SPINA-GD index remained at a similar level throughout the study.Conclusions The results of the study suggest that the effect of atorvastatin therapy on thyroid autoimmunity depends on vitamin D status.
Keywords: 25-hydroxyvitamin D; thyroid autoimmunity; statins; vitamin D status